Combination of geographical and socio-economic proximities - Eric Boutroy; Philippe Bourdeau; Pascal Mao; Nicolas Senil (Revue de Géographie Alpine)
While it is today acknowledged that the Rhône-Alpes region is characterised by a singular concentration of sport-related firms, specialising particularly in the mountain and nature sports sector, the phenomenon does not appear to fall within classic paradigms for analysing the territorialised interrelationships between actors in the fields of industry, research and training. Such observations do not imply the absence, in Rhône-Alpes, of strong interaction between geographically close actors, but rather prompt a more descriptive and measured approach in addressing the phenomenon. On the basis of the results of a study cross-cutting economic geography and cultural geography, this article will first show how the Rhône-Alpes region sustains a leading “mountain and nature sports tourism” commodity chain, by detailing its structural and territorial features, including broadened spatial scale, plurality of actors and interrelated functions. As part of a comprehensive approach, an attempt will then be made to show the existence of localised cooperation configurations, based on complementarity of geographical and socio-economic proximities. At a time when centralised public cluster policies are coming under question (Duranton et. al., 2008), it would seem legitimate to observe the “spontaneous” dynamics between organisations, in order to gain a more realistic understanding of the link between the attractiveness of the region’s territories and the competitiveness of a commodity chain.